Personal Analgesic List Definition in Accordance with the Rational Use of Medicine for Dentistry - AKICI, AHMET; GÖÇMEN, GÖKHAN (MARMARA UNIV, FAC PHARMACY, 2017)
Physicians should prepare their own personal medicine list for each indication before consulting with patients. This approach is essential for rational use of medicine (RUM). One of the most commonly prescribed medicine groups by dentists is analgesics. The purpose of this review is to indicate how to perform medicine selection based on RUM principles. It is explained with the integration of personal analgesic list (PAL) concept to dentistry. PAL establishment is based on 4 main criteria, which are efficacy, safety, suitability and cost, and the knowledge of clinical pharmacology of analgesics. These principles are followed to choose the best alternative through all medicines. Therefore, dentists might minimize their necessity of knowledge about various kinds of analgesics. It will be easier to learn limited number of medicines in the PAL. In this method, dentists will precisely wise up about a few numbers of medicines, select the most proper one through them and easily remember every details of information that should be given to their patients. Consequently, a dentist with PAL will be able to perform a successful analgesic treatment. This rational approach, initiated with analgesics, might be used by the help of transfer effect in other medicine/product groups, such as antibiotics.
Keywords: Dentist; Rational use of medicine; Efficacy; Safety; Suitability; Medicine choosing; NONSTEROIDAL ANTIINFLAMMATORY DRUGS; PAIN